2019
DOI: 10.1016/j.ijheatmasstransfer.2019.118675
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inhomogeneous porosity on effusion cooling

Abstract: Effusion cooling is an effective cooling technology which is considered as the next logical step of the cooling technology for gas turbine blades. Additive manufacturing technology makes it possible to fabricate effusion cooling structures in gas turbine blades with the optimal parameters and a low cost. However, the sizes of cooling holes were usually inhomogeneous owing to the limited accuracies of additive manufacturing technology. This study investigated the influence of inhomogeneous porosity on effusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Normally, the row-to-row interaction of the coolant jets benefits the film cooling performance since the kidney vortices can be countered to some extent by the secondary vortices from the holes in the next row. Huang and He (2019) numerically investigated the effect of inhomogeneous porosity on effusion cooling performance. The results showed that the high heat conduction inside the solid reduced the inhomogeneous effect, while the inhomogeneous porosity had a remarkable effect on the local effusion cooling efficiency when a low thermal-conductivity Thermal Barrier Coating (TBC) covered the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the row-to-row interaction of the coolant jets benefits the film cooling performance since the kidney vortices can be countered to some extent by the secondary vortices from the holes in the next row. Huang and He (2019) numerically investigated the effect of inhomogeneous porosity on effusion cooling performance. The results showed that the high heat conduction inside the solid reduced the inhomogeneous effect, while the inhomogeneous porosity had a remarkable effect on the local effusion cooling efficiency when a low thermal-conductivity Thermal Barrier Coating (TBC) covered the surface.…”
Section: Introductionmentioning
confidence: 99%